Resources productivity and resource use efficiency of milk production in Bulandshahr district of Uttar Pradesh - SHAH, DEEPAK; SINGH, PARMATMA (The Indian Journal of Animal Sciences, 2013)
The factor-product relationship in the use of resources for milk production through different breeds of buffaloes was studied in Bulandshahr district of Uttar Pradesh during 1989-90. The Cobb Douglas production function revealed that concentrate was the most significant input influencing milk output. The green and dry fodder inputs also influenced milk production positively in almost all the seasons. The stage of lactation showed its negative impact on milk yield while the value of animal was positively associated with milk production through buffaloes. The marginal value product of concentrate showed that in almost all the cases it was used efficiently to a considerable extent in Murrah buffaloes. However, the use of green fodder input wa.s efficient only in rainy season for local buffaloes. A readjustment in resource use was suggested for accelerated milk production through buffaloes in the study area.